Branching Morphogenesis - Horowitz, Arie; Simons, Michael (Circulation research, 2008)
Tubular structures are a fundamental anatomic theme recurring in a wide range of animal species. In mammals, tubulogenesis underscores the development of several systems and organs, including the vascular system, the lungs, and the kidneys. All tubular systems are hierarchical, branching into segments of gradually diminishing diameter. There are only 2 cell types that form the lumen of tubular systemseither endothelial cells in the vascular system or epithelial cells in all other organs. The most important feature in determining the morphology of the tubular systems is the frequency and geometry of branching. Hence, deciphering the molecular mechanisms underlying the sprouting of new branches from preexisting ones is the key to understanding the formation of tubular systems. The morphological similarity between the various tubular systems is underscored by similarities between the signaling pathways which control their branching. A prominent feature common to these pathways is their duality—an agonist counterbalanced by an inhibitor. The formation of the tracheal system in Drosophila melanogaster is driven by fibroblast growth factor and inhibited by Sprouty/Notch. In vertebrates, the analogous pathways are fibroblast growth factor and transforming growth factor-β in epithelial tubular systems or vascular endothelial growth factor and Notch in the vascular system.